2003
DOI: 10.1016/s1569-9293(03)00049-5
|View full text |Cite
|
Sign up to set email alerts
|

Benign intramural schwannoma of the oesophagus: a diagnostic pitfall

Abstract: A 33-year-old man underwent resection of a benign intramural schwannoma of the oesophagus. Similar clinicopathological and immunohistological features prompted a review of an earlier case initially diagnosed as a S-100 negative leiomyosarcoma. This stained positive using a new S-100 immunohistochemical antibody (Dako, Trappes, France). The frequency of these extremely rare tumours may be higher than initially thought. Pitfalls for the surgeon are highlighted and attention is brought to a recent consensus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Endoscopic ultrasonography-guided fine needle aspiration biopsy is not always useful for diagnosis, as in our cases [ 1 ]. The value of frozen section is limited, and it can lead to diagnostic pitfalls [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic ultrasonography-guided fine needle aspiration biopsy is not always useful for diagnosis, as in our cases [ 1 ]. The value of frozen section is limited, and it can lead to diagnostic pitfalls [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical excision of the tumor is the method of choice, because chemotherapy and radiotherapy are ineffective. The option of enucleation is recommended when: the tumor is well encapsulated, a clear margin is achievable, and there is sufficient redundant mucosa to close the defect [ 6 ]. In our case we removed the tumor without damage to the mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Complete excision of a schwannoma is curative. 18 It is possible to enucleate the tumor with part of the esophageal mucosa and close the injured esophageal mucosa and the muscle layer without reconstruction. Hamoir et al reported enucleating a CES as large as 8 cm.…”
Section: Discussionmentioning
confidence: 99%